2016
DOI: 10.1177/0263774x16646772
|View full text |Cite
|
Sign up to set email alerts
|

From liability to opportunity: An institutional approach towards value-based land remediation

Abstract: The remediation of contaminated sites impacts on stakeholders in potentially beneficial ways, yet stakeholder dialogue has historically been focussed on costs, risk, liability, stigma, and other negatives. Shedding light on stakeholders’ remediation values can help reform remediation policy towards more positive outcomes of site clean-up. We adopt institutional theory to elicit plural motivations and cognitive assumptions as embedded in stakeholders’ expressions of remediation values, objectives, and outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(88 reference statements)
0
5
0
1
Order By: Relevance
“…In some cases, sanctions for the illegal removal of ecologically mature trees are inadequate or not enforced. In this case, the costs of retention exceeds the costs of compliance and the payoff of breaking the rules is vindicated in the mind of the proponents [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, sanctions for the illegal removal of ecologically mature trees are inadequate or not enforced. In this case, the costs of retention exceeds the costs of compliance and the payoff of breaking the rules is vindicated in the mind of the proponents [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ecologically mature trees in Australian cities, often several centuries old, represent an exclusive habitat for many species and are key structures for conserving species in urban settings [23]. Yet recent research has indicated that ecologically mature trees are declining within intensively-managed urban and peri-urban landscapes [14].…”
Section: Ecologically Mature Trees In Canberra Australiamentioning
confidence: 99%
“…This is seen as being problematic in two ways, firstly that it may not sufficiently include discourse from Humanities disciplines, and secondly that, for the purposes of community engagement in sustainability assessment, may not be fully representatives of the "values" that impacted communities may wish to convey, or not be formulated in a way that community participants can readily engage with. Furthermore, interaction in describing and communicating values can be educational for both expert and non-expert alike and support constructive engagement [68,71,[96][97][98]. This may be of great value for some particularly sensitive remediation projects.…”
Section: Discussionmentioning
confidence: 99%
“…Australia/Fiji 2016 An academic study of how different groups of stakeholders perceive different values for remediation, and that these can change as a project progresses, which took place across four case studies [68].…”
Section: Country/region Application Commentsmentioning
confidence: 99%
“…The various community values will need to be reconciled with technical opinions and also the legitimate concerns of other stakeholders (such as the site owner, the regulator, etc. ), which may be challenging (e.g., Plant et al, 2017). Anecdotal information from CL:AIRE members suggests that these wider concerns may be related to the built development that is facilitated by the remediation, and can be a major obstacle to relationship building, even though the impact of concern is not directly related to the implementation of the remediation per se, but rather what it facilitates.…”
Section: Revised Surf‐uk Indicatorsmentioning
confidence: 99%